Public Sector Organizations’ Performance Evaluation Via Customer Satisfaction Approach: Twin-Client Scenario with Competing Interests: The Case of Pakistan’s FTO (Journal of Asian Development Studies, 2017)
The paper, inter alia, attempts to dissect the causes of friction between two very important institutions within the extractive machinery of Pakistan i.e. FTO, and FBR. In this connection, the precise hypothesis that the paper looks to test is: “The Federal Tax Ombudsman transgresses its lawful jurisdiction to redress the taxpayers’ complaints.” In order to test the hypothesis two elaborate survey questionnaires were devised to separately target both of the FTO’s clients. Like all rigorous research projects, the paper also tries to add to the process of knowledge development and provide empirical basis to the general perceptions, and help illuminate meaningful discussion in the policy formulation circles of Pakistan in the years to come. In this respect, the paper seminally looks to apply Customer Satisfaction Approach (CSA) in the twin-client scenario with competing interests which FTO’s business model offers. The “twin-client scenario with competing interests” actually refers to the heart and soul of the research project by suggesting that, in fact, FTO’s clients are two: (i) the taxpayer and (ii) the tax-collector. The paper takes the first client (taxpayer) as the utility-maximizing individual, and the second client as the revenue-maximizing leviathan. The underlying assumption, when articulated in technical terms, is that it is a zero-sum scenario – wherein the aggregate size of the pie remains the same and one loses or wins only at the cost of the other. This is where, the literature on organizational theory surveyed, reveals that the paper has an ample space to contribute to the existing knowledge pool on organizational theory and development. On the basis of the data collected, the paper attempts to see as to how the twin-client scenario in competing interests resolves itself – or even does it? In fact, the conclusion as arrived at by the paper on the basis of the data is that CSA cannot per se be applied to organizations operating in a twin-client scenario with competing interests – including courts at all levels and of all types.